Respon Respon Pertumbuhan dan Hasil Tanaman Kale (Brassica oleracea L.) Terhadap Frekuensi dan Dosis Pupuk NPK Dalam Bentuk Enkapsulasi - Fachrurrozi, Faisal; Saputr, Tri Wahyu; Suci Ristiyana; Bowo, Cahyoadi (Jurnal Agroekoteknologi dan Agribisnis, 2025)
Encapsulation in the combination of specification components with additional elements to create a capsule as a protective material. NPK fertilizer is one of the inorganic fertilizers that is used very efficiently in increasing the availability of macro nutrients N, P, and K replacing single fertilizers which are sometimes difficult to obtain and very expensive. Kale itself is a plant that is rich in nutrients, moreover it contains many high antioxidants and other good compounds and is also classified as a superfood plant. However, the development in Indonesia is still low due to land degradation and fertilizers that have been contaminated by other materials. The use of encapsulation in fertilizers is needed because it provides many benefits such as increasing soil binding capacity to water, facilitating root growth, storing water longer, efficient use and can be used in agricultural land, plantations, and critical land reclamation. The provision of NPK encapsulation can increase the effectiveness of plants, increase the substance of soil humus, growth hormones, enzymes and organic compounds in the soil. This study used a completely randomized design with two factors, namely the frequency of fertilization (once, twice, and thrice). The second factor is the encapsulation dose with 4 levels including control, 10, 15, and 20 gram. The results showed the best results in N1P1 for plant height, N1P2 for plant fresh weight with a dose of 10 grams and a fertilization frequency of 1 time and a dose of 10 grams and a fertilization frequency of 2 times. Giving a dose of NPK encapsulation of 10 grams (N1) is proven to increase growth and yield in kale plants and can be recommended as an alternative to kale plant cultivation.